Hoe beleef pasiente hul verpleegsorg? - M. V. Vermaak (AOSIS, 1981)
A descriptive survey was undertaken to find out whether nurses in five training schools for general nurses fulfilled the needs of their patients in regard to physical care, orientation and teaching and emotional support. The findings suggest that there is room for improvement especially tion, patient teaching and emotional support. Recommendations to facilitate improv ienm oerniet natraemade.